A new dromiid crab (Crustacea, Brachyura, Dromioidea) from the Upper Eocene of Huesca (Aragón, northern Spain) - Artal, Pedro; Bakel, Barry W.m. Van; Domínguez, José L.; Gómez, Guillermo (Zootaxa, 2016)
A new genus and species of brachyuran crab from the Upper Eocene (Priabonian) strata in Basa Valley (Huesca, northern Spain) assignable to the superfamily Dromioidea, Basadromia longifrons n. gen., n. sp., adds to current knowledge of the morphological diversity and geographical-stratigraphical distribution of the superfamily. The main characters of the new form, such as the orbitofrontal construction with two median teeth and an rostral tooth situated in a lower plane, two minor frontal (inner orbital) teeth, well-marked cervical and branchial grooves, general carapace outline, and the shape and distribution of dorsal regions, confirm placement in Dromioidea. Unique features, such as the four conspicuous frontal teeth, lateral margins of carapace with small, subtle spines, the reduced length of the posterior margin, disposition of dorsal grooves, and peculiar shape and distribution of the dorsal regions (mainly protogastric and epibranchial), warrants the erection of a new genus and new species. In the absence of ventral features the new taxon is tentatively assigned to the family Dromiidae after detailed comparison with both fossil and extant members.